Effectiveness of antihistamines for itch and sleep disturbance in atopic dermatitis: a retrospective cohort study. Issue 2 (18th April 2021) - Tay, Charmaine J.; Zhao, Xiahong; Allen, John C.; Yew, Yik Weng; Tey, Hong Liang
Abstract : Introduction: Atopic dermatitis (AD) is a common and debilitating condition, with pruritus being the hallmark symptom responsible for negative quality of life in AD patients. Oral antihistamines are commonly used to manage itch in AD, but evidence of its efficacy is lacking and debatable. Methods: A retrospective cohort study on patients with AD treated with antihistamines was conducted at the National Skin Centre from January 2015 to December 2018. Severity of disease was measured using the SCORing Atopic Dermatitis (SCORAD) index. Data was analyzed using a mixed-effects linear model to account for repeated measures on the same individual. Results: There were 161 unique patients with 380 treatment outcomes included in our analysis. Patients who were treated with antihistamines had higher baseline itch and sleep disturbance scores compared with those who were not. We found that the use of antihistamines resulted in significant improvement in itch and sleep disturbance scores with respective mean decreases of 0.67 [95% confidence interval (CI): 0.07, 1.27; P =0.03] and 0.87 (95% CI: 0.22, 1.52; P =0.01) compared with patients not treated with antihistamines. Specifically, second-generation antihistamines improved itch and sleep disturbance scores better than first-generation antihistamines, with a decrease of 0.65 (95% CI: −0.59, 1.88) and 0.61 (95% CI: −0.66, 1.88), respectively, although the difference in effect was not significant. Meanwhile, antihistamine use did not significantly improve total SCORAD and objective SCORAD scores. Conclusion: Treatment with second-generation antihistamines, may be an appropriate treatment modality for managing itch and sleep disturbance in patients with AD.